Pengaruh Gengsi, Tekanan Sosial Media, dan Kontrol Diri Terhadap Perilaku Konsumtif Berlebihan pada Penggunaan Marketplace Shopee - Yolanda Mey Erwadi; Indira Shofia Maulida; Moh. Muklis Sulaeman; Dhita Dora Damayanti (Trending: Jurnal Manajemen dan Ekonomi, 2025)
In this digital era, consumptive behavior is increasing, especially through online shopping platforms such as Shopee. Prestige and social media pressures, such as trends and lifestyles displayed on these platforms, are thought to strongly influence consumer purchasing decisions. In contrast, self-control is expected to be an inhibiting factor for excessive consumptive behavior. This study aims to analyze the influence of prestige, social media pressure, and self-control on excessive consumptive behavior in Shopee marketplace users. This research uses a quantitative approach with a survey method. Samples were taken randomly from active Shopee users with certain criteria. Data were collected through a questionnaire that measured the variables studied, namely prestige, social media pressure, self-control, and excessive consumptive behavior. Data analysis was carried out using multiple linear regression techniques to test the research hypothesis. The results showed that prestige, social media pressure, and self-control have a positive and significant influence on excessive consumptive behavior in using the Shopee marketplace. This indicates that the higher the perceived prestige and social media pressure, the higher the tendency of consumers to behave excessively consumptively. Conversely, the higher the self-control, the lower the tendency. This research provides practical implications for consumers to be more aware of the factors that influence their consumptive behavior, as well as for Shopee to develop more responsible marketing strategies and features that support consumer self-control.